Reliability Analysis Diagnostic Mathematics Test at the National University of Costa Rica - Zamora Araya, José Andrey (2015)
The goal of this study is to show how the implementation of the theory of item response, particularly the Rasch model has improved the reliability indices math test diagnosis at the National University of Costa Rica, from an alpha of 0.51 in 2010 to one of 0, 78 in 2012. The psychometric analysis allowed providing recommendation regarding the construction of the test which resulted in better indicators and preparation of items to measure the different levels of skill that is the fundamental purpose of a diagnostic test.